2018
DOI: 10.1148/radiol.2018171116
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Radiation Force Impulse US Imaging: Liver Stiffness in Patients with Chronic Hepatitis B with and without Antiviral Therapy

Abstract: Purpose To investigate the clinical utility and longitudinal change of acoustic radiation force impulse (ARFI) ultrasonographic (US) imaging in patients with chronic hepatitis B. Materials and Methods A retrospective cohort study of patients with chronic hepatitis B who underwent serial ARFI examinations in a tertiary referral center in Taiwan between 2012 and 2016 was conducted. The clinical information and noninvasive liver stiffness measurement tests (ARFI, Fibrosis-4 index [FIB-4], and FibroScan) were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Additionally, the volume of hepatocytes accounts for more than 90% of the total volume of the liver, with liver function being more severely affected in HBV-infected patients than in those with IPH. In the liver, there is mostly inflammation, thick fibrous septa, and small nodules, which are the most important factors for the LS increase [ 19 ], as found in our study (Table 2 ). However, at the later stages, with the progression of hepatocytes death, extracellular matrix deposition, and vascular reorganization, the pathological hallmark of the liver is pseudolobule formation, which includes regenerative nodules, fibrous septa, and microvascular clotting [ 16 ].…”
Section: Discussionsupporting
confidence: 75%
“…Additionally, the volume of hepatocytes accounts for more than 90% of the total volume of the liver, with liver function being more severely affected in HBV-infected patients than in those with IPH. In the liver, there is mostly inflammation, thick fibrous septa, and small nodules, which are the most important factors for the LS increase [ 19 ], as found in our study (Table 2 ). However, at the later stages, with the progression of hepatocytes death, extracellular matrix deposition, and vascular reorganization, the pathological hallmark of the liver is pseudolobule formation, which includes regenerative nodules, fibrous septa, and microvascular clotting [ 16 ].…”
Section: Discussionsupporting
confidence: 75%
“…The performance of transient elastography in chronic hepatitis B was described in the last WFUMB guidelines (Ferraioli et al 2015). Since then, 2-D SWE (Leung et al 2013;Zeng et al 2017) and p-SWE (Hu et al 2017;Kim et al 2016;Su et al 2018) have also been evaluated against liver histology in patients with chronic hepatitis B. Overall, studies have indicated similar diagnostic accuracy across different machines.…”
Section: Hepatitis Bmentioning
confidence: 99%
“…Longitudinal follow-up studies have shown a significant decrease in shear wave velocity measurements both in patients with significant fibrosis and cirrhosis. 8 We should however note that this change was noted only after 32 months of antiviral therapy. 9 …”
mentioning
confidence: 96%